COMMUNITY DEVELOPMENT THROUGH SOCIAL ASSISTANCE IN THE DISTRICT. MEDAN DENAI, MEDAN CITY - Shintia Putri Aisyah; Bachtiar Ahmad Fani Rangkuti (Universitas 17 Agustus 1945 Surabaya, 2023)
Community development, which seeks to increase participation and a sense of participation and belonging together in the program to be implemented, must also contain elements of community empowerment. Empowerment refers to the ability of people, especially vulnerable or weak groups, to have access to productive sources that enable them to increase their income and obtain the goods and services they need and then participate in the development process and decisions that affect their environment. or themselves. In reality, this process often does not appear automatically, but rather grows and develops based on the interaction of local communities with external parties or social workers who work based on charitable encouragement or a professional perspective. These social workers act as social assistants. Who is present as an agent of change who is involved in helping solve the problems they face. Social assistance can be interpreted as a dynamic interaction between poor groups and social workers to jointly face various or various challenges. Community development is also interpreted as a strategy of choice in the context of alternative development, while the concept of alternative development in development discourse is then a reaction to the weaknesses of the development model, also overcoming the problem of poverty, preserving the environment and solving strange social problems that oppress society.